Rituais online: fermento para a espiritualidade do self e a novaerização das religiões - Hida, Ricardo Toshio Bueno (2023)
This dissertation aims to investigate the importance of online rituals in strengthening the religion of the self and how they collaborate with the greater, unintentional presence of the New Age ethos in traditional religions. The online ritual is a natural and automatic consequence of a network society in which the internet proposes a new temporal and spatial logic, transforming the dynamics of relationships, including in the religious environment. The New Age, otherwise, as a movement that captured changes in the way individuals have been trying to deal with their spiritual needs, has its own ethos that translates the almost narcissistic individualization, the logic of increasing consumption of symbolic goods, the sacralization of psychology and the resignification of religious authority in the current scenario of religious pluralism. This research initially discusses the characteristics of online rituals from anthropological studies on rituals, then seeks to understand the Novaerist movement from its historical context and the meaning of the New Age ethos category Finally, the dissertation presents the importance of the online religious ritual in the spirituality of the self and its role, within the New Age ethos that have been observed more and more frequently in traditional religions, such as Catholicism, evangelical churches and also in Umbanda